Pharmacological Treatment of Multiple Sclerosis - Oliveira, Paulo Diniz de; Deuner, Melissa Cardoso; Rodrigues, Andréa Fernanda Luna (JRG Journal of Academic Studies, 2024)
Objective: To discuss the relevance of pharmacological treatment for multiple sclerosis and highlight the importance of the pharmacist's role in therapeutic management. Methodology: The literature review was conducted using databases such as the CAPES Theses and Dissertations Catalog, The Scientific Electronic Library Online (SciELO), and Google Scholar. The inclusion criteria for the articles and studies selected were publications in Portuguese or English from the years 2019 to 2024. Results: The effectiveness of pharmacological treatments depends not only on the medications used but also on pharmaceutical support, which has proven essential for improving treatment adherence and minimizing adverse effects. Patient education about the disease and treatment is an area where pharmacists can make a significant difference. Conclusion: The pharmacist's role in managing multiple sclerosis is essential to optimize pharmacological treatment and ensure that patients receive the necessary support. The research underscores the importance of integrating pharmacists into the healthcare team, highlighting the need for further studies to deepen understanding of this role.